DESIGN, CONSTRUCTION AND TEST OF GAMMA IONIZATION CHAMBERS. Issue 20 (9th October 2022) - Zhang, Weihua; Zhang, Yi; Sun, Mingyan; Zhu, Meiling; Huang, Xianchao; Tong, Teng; Li, Daowu
Abstract: Ionization chamber is considered as the golden standard for the dosemeter. This work fabricated one graphite-walled and two polymethyl methacrylate (PMMA)-walled ionization chambers, tested respectively and compared their characteristic parameters. The performance of graphite-walled chamber was similar to that of the PMMA-walled chamber. The relative energy response of ionization chambers was lower than 4% from 50 keV to 50 MeV based on the FLUKA code simulation results. The experimental data showed that the ionization chambers performed well in linearity and repeatability. Assuming the chambers sensitive volume and HV bias was constant, the measured maximum saturation absorbed dose of ionization chambers changed with the diameter variation of chambers anode based on the comparison results of two PMMA-walled ionization chambers.